Implementasi Web E-Commerce Berbasis Content Management System Wordpress pada DND Komputer - Witi, Ferdinandus Lidang; Mude, Anastasia (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Research from research institute in Germany, the projected e-commerce growth in Indonesia is 30.5%. The development of internet users in Indonesia will increase by 1.5 million people in 2023. This shows that more than 50% of Indonesian people use e-commerce. DND Computer is a shop that sells electronic products, especially laptops, PC, computer network equipment, printers, and computer accessories. The sales process is carried out on-site or manually where consumers come directly to the shop. This is the problem raised in this article create an e-commerce website based on a content management system to make it easier for consumers to make purchases online. The research stages used were problem identification, data collection, needs analysis, e-commerce modeling, and implementation of an e-commerce website. After all the data is obtained, prepare a Canva Business Model first to give you an overview of the e-commerce website modeling that will be built. The e-commerce website that is being built will help DND Computer owners in running their business and this website is a form of digital marketing that will bring in lots of customers and make transactions easier. Keywords : e-commerce, content management system, CMS WordPress website.